2020
DOI: 10.2196/20828
|View full text |Cite
|
Sign up to set email alerts
|

Real-Time Digital Contact Tracing: Development of a System to Control COVID-19 Outbreaks in Nursing Homes and Long-Term Care Facilities

Abstract: Background Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) can spread rapidly in nursing homes and long-term care (LTC) facilities. Symptoms-based screening and manual contact tracing have limitations that render them ineffective for containing the viral spread in LTC facilities. Symptoms-based screening alone cannot identify asymptomatic people who are infected, and the viral spread is too fast in confined living quarters to be contained by slow manual contact tracing processes. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
34
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(36 citation statements)
references
References 48 publications
0
34
0
Order By: Relevance
“…Assuming R eff = 2.6, digital tracing at a 60% adoption rate would produce a 67% reduction in peak incidence. Finally, Wilmink, Summer, and Marsyla (2020)) reported 12% fewer infections for 100% uptake. This study refers to nursing homes and long-term care facilities, and population uptake refers only to personnel, residents, and visitors.…”
Section: Resultsmentioning
confidence: 95%
See 3 more Smart Citations
“…Assuming R eff = 2.6, digital tracing at a 60% adoption rate would produce a 67% reduction in peak incidence. Finally, Wilmink, Summer, and Marsyla (2020)) reported 12% fewer infections for 100% uptake. This study refers to nursing homes and long-term care facilities, and population uptake refers only to personnel, residents, and visitors.…”
Section: Resultsmentioning
confidence: 95%
“…Of the eight papers, four reported that digital contact tracing alone (i.e., without manual tracing) reduces significantly infections or R eff more than manual tracing ( Abueg et al, 2021 ; Ferretti et al, 2020 ; Kretzschmar & Rozhnova, 2020 ; Wilmink et al, 2020 ), and two reported only a marginal improvement of R eff ( Bradshaw et al, 2021 ; Plank et al, 2020 ). For example, without manual contact tracing, digital tracing reduces R eff from 2.4 to 1.46, while manual contact tracing (in the absence of digital) reduces R eff to 1.5 ( Plank et al, 2020 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…based on a predicted distance and the duration of the contact), and to notify potentially exposed people using a centralized or decentralized network approach (John Leon Singh, Couch, & Yap, 2020). Efficacy of digital contact tracing systems has been assessed in previous studies thus reinforcing the idea that these tools can help limit the spread of the virus (Kretzschmar et al, 2020;Wilmink et al, 2020).…”
Section: Introductionmentioning
confidence: 99%